Patterns of Human Immunodeficiency Virus Type 1 Recombination Ex Vivo Provide Evidence for Coadaptation of Distant Sites, Resulting in Purifying Selection for Intersubtype Recombinants during Replication - Galli, Andrea (American Society for Microbiology (ASM), 2010)
High-frequency recombination is a hallmark of HIV-1 replication. Recombination can occur between two members of the same subtype or between viruses from two different subtypes, generating intra- or intersubtype recombinants, respectively. Many intersubtype recombinants have been shown to circulate in human populations. We hypothesize that sequence diversity affects the emergence of viable recombinants by decreasing recombination events and reducing the ability of the recombinants to replicate. To test our hypothesis, we compared recombination between two viruses containing subtype B pol genes (B/B) and between viruses with pol genes from subtype B or F (B/F). Recombination events generated during a single cycle of infection without selection pressure on pol gene function were analyzed by single-genome sequencing. We found that recombination occurred slightly (∼30%) less frequently in B/F than in B/B viruses, and the overall distribution of crossover junctions in pol was similar for the two classes of recombinants. We then examined the emergence of recombinants in a multiple cycle assay, so that functional pol gene products were selected. We found that the emerging B/B recombinants had complex patterns, and the crossover junctions were distributed throughout the pol gene. In contrast, selected B/F recombinants had limited recombination patterns and restricted crossover junction distribution. These results provide evidence for the evolved coadapted sites in variants from different subtypes; these sites may be segregated by recombination events, causing the newly generated intersubtype recombinants to undergo purifying selection. Therefore, the ability of the recombinants to replicate is the major barrier for many of these viruses.